Desenvolvimento de método para determinação de alcaloides indólicos em amostras de ayahuasca - Santos, Mônica Cardoso (2016)
Ayahuasca is a psychoactive beverage prepared by decoction of stems and leafs from Banisteriopis caapi and Psycotria viridis, respectively. Initially, this tea was used by South America Indian tribes, but nowadays, the consumption is spread all over the world due the growth of religious groups where ayahuasca is considered a sacrament. In this work, we propose a method for determination of the alkaloids: Tryptamine, N, N – Dimethyltryptamine, Harmalol, Harmine, Harmaline and Tetrahydroharmine in ayahuasca samples by HPLC/DAD system using Solid Phase Extraction technique as sample preparation. Tests carried out with standard solutions of alkaloids allowed the adjustment of the chromatographic conditions for simultaneous determination of analytes. The best analytic answer for extraction procedure was employing silica cartridge. The validation of the analytical method showed linearity in the range of 0.9950 a 0.9998 and sensitivity in the concentration range of 1-250 μg mL-1 accuracy and precision, with recovery values between 45.0 to 107.4% and variation coefficients between 1.1 to 9.8%; limits of detection and quantification in the range of 6.8 - 18.8 μg mL-1 and 20.6 - 57.1 μg mL-1, respectively. Moreover, the adsorptive capacity of two new solid phases [Biochar and SiMen(M)TSC] was observed with satisfactory recovery results in the range of 40.6 - 116.2 and 45.3 - 115.7%, respectively. The concentrations of these alkaloids were determined in ayahuasca beverage from nonprofit religious cult of the Fortaleza City showed to range from 0.3 to 36.7 g L-1.